Policy Capacity Based on Disaster Mitigation in West Sulawesi - Hassan, Bujaeramy; Maulana, Adi; Idris, Muhammad; Yamin, Muhammad; B, Ahmad Nurzaki Azhar (KnE Social Sciences, 2025)
This study aims to analyze the policy capacity from the institutional, regulatory, technical, and participatory aspects implemented by the government based on disaster mitigation in West Sulawesi. It uses a qualitative descriptive approach to explain regional policy capacity exploration in disaster mitigation case studies. The study was conducted at Regional Disaster Management Agency (BPBD) and Regional Device Organization (OPD) related to disaster mitigation. Data were collected through observation, questionnaires, in-depth interviews with informants, and literature studies. They were then analyzed using the Miles and Huberman approach, which consists of data reduction, data presentation, verification, and conclusion. The results found that the capacity of mitigation-based policies still faces challenges in four main aspects: institutional, regulatory, technical, and participatory. Institutionally, formal structures such as BPBD and related OPDs, coordination, human resources, and inter-agency roles still need to be strengthened. Regulations have not been implemented in a contextual, practical, and integrated manner with regional development planning. Technically, there are still weaknesses in the limitations of facilities, infrastructure, and the use of technology in supporting operations for mitigation activities. Community participation is also not optimal in terms of awareness, active involvement, and ongoing education. Policy recommendations can be submitted, including recommendztions to strengthen local institutions by increasing institutional capacity through periodic human resources training, strengthen cross-sector coordination systems, and establish work units that are adaptive and responsive to the dynamics of disaster risk.